Outline of Hand and Wrist Injuries Presenting to an Emergency of a Tertiary Care Centre in Nepal - Shrestha, Shilu; Tamrakar, Subidha; Banskota, Ashok K (Journal of Nepal Health Research Council, 2019)
Background: Hand and wrist injuries are getting commoner with increasing incidence of injuries and accidents. This study aims to identify the prevalence and pattern of hand and wrist injuries presenting to the emergency department of a tertiary care center of Nepal. Methods: The study was conducted through review of electronic data of the patient in the emergency department database for the period of 1 Nov 2005 till 31 Oct 2015.Data was extracted in Microsoft Excel 2007 andanalyzed to measure incidence and pattern of the hand and wrist injuries. Results: There were2899 number of patients with hand and wrist injuries during the period. Most were males (80%) and commonest age group was 20-29 years. Majority of the injuries were due to road traffic accident (n=786, 27.11%), fall injury (n=696, 24.09%), cut injury with sharps (n=404, 13.94%) and machinery injury (n=319, 11%). The commonest presenting injuries were hand fractures (n=1820, 62.8%) followed by distal radius fracture (n=613, 21.1%), crush injury of hand (n=409, 14.1%), and cut injury (n= 406, 14%). Almost half, 48.84 % cases were discharged from the emergency department with preliminary or definitive management. Conclusions: Hand and wrist injuries constitute a substantial number of casesseen and managed in the emergency department.Therefore, public health measures should be taken to reduce RTI, fall injury and occupational accidents. Andit is of paramount importance that emergency care giver attends these injuries properly and timely and establishes a good referral system as and when necessary. Keywords: Emergency; epidemiology; hand injury; Nepal; wrist injury